Postmodern Feminist Identity Through Artworks By Selected Malaysian Female Artists (2000-2015) - Ling, Clara Boon Ing (2018)
The image of a woman throughout the course of history has always been secluded from the artistic masculine society in art. The urban perspective and postmodern thinking forms a central tension and conflict within new paintings and performances by twenty-first century women artists. The present research will seek to analyse selected artworks and performances of Malaysian female artists between years 2000 to 2015 in the light of postmodern feminism. Undeniably, postmodernism thoroughly reminds locals of the power of the Malaysian culture, which diversifies the identity of women today.